Visual semiotics in the structure of Kufic calligraphy - Kaddour Abdallah Tani (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2021)
In the aesthetic study, semiotic interpretation is an intellectual approach to deciphering the hidden meaning of an aesthetic achievement's taste. The study's goals include comprehending the artwork's structure, which necessitates an in-depth interpretation of the language by translating it into official symbols. This research method uses a linear formation sample with semantic attributes attached to the Kufic calligraphy of artworks. The findings reveal that the emergence of geometric lines in a linear composition has a decorative abstraction that may be used to argue that the artist intended to place it there and that this is a symbol of the cosmos and its existence. This study adds to our understanding of compositional insight in Arabic calligraphy as an expressive aesthetic expression that alludes to the text in the sense of meaning that lies underneath the direct meaning